(untitled) (Perner’s Contacts, 2018)
The safety of inland waterway transport is a complex of interconnected navigation and waterway management systems. Tracking and assessing the quality of waterways depends, in particular, on the amount of shipping accidents and limitations that hinder the smooth transport process. The increase in navigation volumes has a direct effect on increasing the risk of navigation accidents. Tracking and assessing the quality of inland waterways is one of the tools to respond to changes in transport performance as well as an impulse to take the necessary safety measures.